The Kinked Oligopoly Curve Reconsidered - Efroymson, C. W. (Quarterly Journal of Economics, 1955)
Introduction, 119. — I. Belief in the existence of the kink, 119. — II. Price patterns: rigidity, 127; the time period, 128; nominal versus transaction prices, 130; collusion and price leadership, 132; price rigidity of monopolies and heterogeneous oligopolies, 133. — III. Conclusions, 135.